2012
DOI: 10.7314/apjcp.2012.13.10.5027
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Survivin and Caspase 3 in Oral Squamous Cell Carcinoma and Peritumoral Tissue

Abstract: This study was conducted to investigate the expression of survivin and caspase 3 in oral squamous cell carcinoma and peritumoral tissue, and possible pathogenesis mechanisms. We used ELISA and western blotting to detect the protein expression levels of survivin and caspase 3 in tissue. In situ hybridization and real-time PCR were applied to assess mRNA expression levels. In this study, 13 tumor samples and 13 peritumoral tissue samples were collected from oral squamous cell carcinoma patients and 10 normal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Previous studies used immunohistochemical assays to detect the expression of survivin in oral mucosae, and observed that its expression in precancerous lesions that had not yet progressed towards malignancy and had progressed to complete squamous cancer were 33% (10/30) and 94% (15/16), respectively (12,13). Previous studies revealed that survivin gene expression was also present in various precancerous damaged tissues, including oral leukoplakia, colon polyps, mastitis or keratotic dermatitis (14,15). The present study obtained similar results, as the expression levels of survivin were gradually increased during the progression from abnormal cell proliferation to malignant transformation.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies used immunohistochemical assays to detect the expression of survivin in oral mucosae, and observed that its expression in precancerous lesions that had not yet progressed towards malignancy and had progressed to complete squamous cancer were 33% (10/30) and 94% (15/16), respectively (12,13). Previous studies revealed that survivin gene expression was also present in various precancerous damaged tissues, including oral leukoplakia, colon polyps, mastitis or keratotic dermatitis (14,15). The present study obtained similar results, as the expression levels of survivin were gradually increased during the progression from abnormal cell proliferation to malignant transformation.…”
Section: Discussionsupporting
confidence: 79%
“…Increased survivin expression is commonly associated with reduced levels of apoptosis and survival rate, increased proliferative index, recurrence rate, and resistance to chemotherapy and radiotherapy, thereby identifying it as a significant independent prognostic indicator of the poor outcome in patients with most tumor types. The immunopositivity for survivin was completely negative in normal oral epithelium, as observed in other studies by Gayathri et al, 10 Lin et al, 11 Khan et al, 12 Li et al, 13 and Jinbu et al 14 Survivin is generally expressed at high levels in embryonic tissues, but present at lower or non-detectable levels in normal adult tissues due to the presence of differentiated cells. 11 In contrast to our findings, few studies have reported mild nuclear and cytoplasmic expression among sporadic cells of basal and parabasal layers.…”
Section: Discussionsupporting
confidence: 78%
“…Hence, it blocks the apoptosis mediated by caspase-3 and finally leads to the development of OSCC. [ 16 ] In an analysis of caspase-3 level estimation in gastric cancer, the results showed the total absence of caspase-3 activity in gastric cancer and in the peritumoral area. On the other hand, the normal mucosa divulged the caspase-3 activity, and it was suggested that lack of caspase-3 activation is involved in the transformation to gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%